2019
DOI: 10.1111/age.12770
|View full text |Cite
|
Sign up to set email alerts
|

Effective genetic markers for identifying the Escherichia coli F4ac receptor status of pigs

Abstract: The F4ac receptor locus (F4acR), which encodes susceptibility or resistance to Escherichia coli diarrhoea, is inherited as an autosomal recessive monogenetic trait. F4acR is localized on pig chromosome 13 (SSC13q41-q44) near the MUC13 gene. Two flanking markers (CHCF1 and ALGA0106330) with a high linkage disequilibrium (LD) with F4acR were found to be effective for the genetic identification of F4ac-resistant pigs in the Swiss Large White breed (one recombinant out of 2034 genotyped pigs). Three recombinant bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Additionally, in order to characterize the diarrhea susceptibility in the cohort based on known genetic risk loci, the FUT1 , rs335979375, polymorphism associated with resistances to ETEC F18 (Meijerink et al., 1997), and the CHCF1, rs340488770, marker associated with resistance to ETEC F4ab/ac (Hu et al., 2019) were genotyped using TaqMan‐based assays. Allele calling was performed on an Mx3000P qPCR System (Agilent, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in order to characterize the diarrhea susceptibility in the cohort based on known genetic risk loci, the FUT1 , rs335979375, polymorphism associated with resistances to ETEC F18 (Meijerink et al., 1997), and the CHCF1, rs340488770, marker associated with resistance to ETEC F4ab/ac (Hu et al., 2019) were genotyped using TaqMan‐based assays. Allele calling was performed on an Mx3000P qPCR System (Agilent, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The identification of genetic factors that influence the development of PWD can provide information that could be useful for risk assessment, treatment strategy selection, breeding, and/or disease prevention. In previous studies, resistance to E. coli F4ab/F4ac and E. coli F18 adhesion has been shown to be inherited as autosomal recessive traits (Bertschinger et al, 1993;Gibbons et al, 1977) and polymorphisms on SSC13 and SSC6 have been shown to co-segregate with E. coli F4 and F18 diarrhea, respectively (Hu et al, 2019;Meijerink et al, 1997). Despite the evidence provided with regard to the genetic etiology of ETEC, it is important to study this aspect further because of the multifactorial nature of PWD.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was conducted in accordance with Swiss guidelines for animal welfare and was approved by the Swiss cantonal veterinary office (approval number: 2016_14_FR). To determine their susceptibility or resistance to ETEC F4ac, genotyping was performed on ear biopsies from week-old piglets [16]. Then, 72 Large White male and female piglets susceptible to ETEC F4ac were selected for the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…vet., MSD Animal Health GmbH, Lucerne, Switzerland), a suspension for injection that contains deactivated fimbria adhesins of E. coli F4ab, F4ac, F5, F6, and the LT-toxoid. To determine their susceptibility or resistance to ETEC F4ac, genotyping was performed on ear biopsies (TypiFix TM , Agrobiogen GmbH, Hilgertshausen, Germany) from week-old piglets originating from the Agroscope sow herd [16]. Briefly, piglets DNA was extracted using QIAamp DNA Mini Kit (Qiagen GmbH, Hilden, Germany).…”
Section: Animals and Housingmentioning
confidence: 99%